Sistem Aplikasi Peminjaman Kendaraan Bermotor PT Trans Mitra Nusantara - Pratama, Riskal Septiawan; Arifin, Agus Kodir; Puspitasari, Anggun Citra Dini Dwi (Program Studi Teknik Informatika Universitas Pamulang, 2020)
A vehicle loan system must be able to carry out its operational activities in an effective and efficient manner. PT TRANS MITRA NUSANTARA is still using the manual method in the loan data collection process, for this reason, a computerized system has been proposed, the Vehicle Loan Application System. The analysis used utilizes the Qualitative Method as a research method carried out by conducting observations, interviews, to find data, obtain, collect or record data that can be used for purposes, and factors related to the subject matter so that a truth will be obtained from the data which is obtained. The results obtained can be concluded that the vehicle lending application system can assist employees in processing input data, and the process of vehicle lending transactions and accelerate the process of making vehicle lending reports.